Extraction, phytochemistry, nutritional, and therapeutical potentials of rice bran oil: A review - Mtabazi G. Sahini; Eric Mutegoa (Elsevier, 2023)
Background: Rice is the third-most-produced crop in the world after corn and sugarcane, and due to its widespread production, its byproduct, rice bran, is widely available. One option to add value to this agricultural waste is by utilizing the potential phytochemicals in rice bran oil (RBO). Rice bran oil contains vital chemicals with medicinal and nutritional benefits. This paper examines the numerous ways that rice bran oil is extracted, the various phytochemicals that are present, as well as their potential for use in nutrition and medicine. Method: A review of literatures released from 1996 to 2023 was done, with just one more item of literature from 1973. The search was performed in various online platforms such as Google Scholar, PubMed, Science Direct, Springer, Research4Life, Web of Science, SciFinder, Science Open etc. The more recent literatures were given more consideration, and the older literatures were only taken into account when they were absolutely essential in light of the subject at hand. Results: Literature survey has revealed that the essential phytochemical components of RBO includes phenolic acids, flavonoids, γ-oryzanol and ferulic acids and vitamin E which constitutes tocopherols and tocotrienols as well as other unique fatty acids. Numerous therapeutical potentials, including antioxidant, anti-inflammatory, antidiabetic, and anticancer activities have been evidenced, thanks to these significant phytochemical ingredients. Additionally, numerous nutritional potentials of RBO have been researched and reported. Conclusions: This review consolidates information on the developments in RBO extraction techniques, phytochemical components, and their nutritional and medicinal benefits. Also included are the approach towards processing of rice bran. Considering the abundance and potential of this agrowaste, the use of RBO based phytochemicals for nutritional and therapeutic purpose is worthy pursuing further.